LA GRAFOMOTRICIDAD COMO TÉCNICA PARA POTENCIAR EL DESARROLLO DE LA MOTRICIDAD FINA EN LOS NIÑOS Y NIÑAS DE 05 AÑOS DE LA INSTITUCIÓN EDUCATIVA INICIAL N°103 PEDRO RUIZ GALLO-2023. - Diaz Vega, Lourdes Rocio (2023)
This research report stems from the challenges observed during preprofessional practice, leading to the fundamental question: What is the impact of graphomotricity as a technique on the development of fine motor skills in fiveyear-old children at I.E.I. N° 103 Pedro Ruiz Gallo-2023? The primary objective is to demonstrate the extent of graphomotricity’s influence as a technique in enhancing the development of fine motor skills. The methodology used is quantitative, of an applicative type, with a pre-experimental design. The study population consisted of 133 children, with a sample of 18 children, and an evaluation rubric was utilized. The pretest results indicated that 100% of the children were in the initial category. In the post-test, 45% achieved the achieved category, and 56% reached the outstanding category. The comparison between the pretest and post-test showed a significant difference, suggesting that graphomotricity as a technique positively impacts the development of fine motor skills. The analysis supports the notion that graphomotricity contributes to the development of fine motor skills in fiveyear-old children. Keywords: Graphomotricity, motricity, fine motor skills, development, enhance.